2015
DOI: 10.5535/arm.2015.39.6.914
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effect of Extracorporeal Shock Wave Therapy According to Treatment Session on Gastrocnemius Muscle Spasticity in Children With Spastic Cerebral Palsy: A Pilot Study

Abstract: ObjectiveTo investigate the therapeutic effect of extracorporeal shockwave therapy (ESWT) according to treatment session on gastrocnemius muscle spasticity in children with spastic cerebral palsy (CP).MethodsTwelve children with spastic CP underwent 1 ESWT and 2 sham ESWT sessions for gastrocnemius (group 1) or 3 ESWT sessions (group 2) once per week for 3 weeks. Modified Ashworth Scale (MAS) score, passive range of motion (PROM) of the ankle plantar-flexor muscles with knee extension, and median red pixel int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 30 publications
0
39
0
Order By: Relevance
“…In the last five years, a few review studies have provided primary evidence to support the use of ESWT for the upper and lower limb spasticity: one meta-analysis of clinical trials on all types of spasticity in patients after brain injury, 40 two meta-analyses of randomized controlled trials (RCTs) on spasticity in post-stroke patients, 41,42 one narrative review on muscle hypertonia and dystonia, 43 and one authorized narrative review on upper and lower limb spasticity in post-stroke patients. 44 Additionally, several studies have confirmed utility of ESWT in reducing spasticity among patients with cerebral palsy (CP, 8 studies on the total sample of 124 patients, 4 used fESWT and 4 rESWT) [45][46][47][48][49][50][51][52] and multiple sclerosis (MS, 1 study involved a group of 34 patients treated with rESWT). 53…”
Section: Current Evidence On Shock Wavesmentioning
confidence: 99%
“…In the last five years, a few review studies have provided primary evidence to support the use of ESWT for the upper and lower limb spasticity: one meta-analysis of clinical trials on all types of spasticity in patients after brain injury, 40 two meta-analyses of randomized controlled trials (RCTs) on spasticity in post-stroke patients, 41,42 one narrative review on muscle hypertonia and dystonia, 43 and one authorized narrative review on upper and lower limb spasticity in post-stroke patients. 44 Additionally, several studies have confirmed utility of ESWT in reducing spasticity among patients with cerebral palsy (CP, 8 studies on the total sample of 124 patients, 4 used fESWT and 4 rESWT) [45][46][47][48][49][50][51][52] and multiple sclerosis (MS, 1 study involved a group of 34 patients treated with rESWT). 53…”
Section: Current Evidence On Shock Wavesmentioning
confidence: 99%
“…Nevertheless, there were some important limitations, for example, the large number of ESWT sessions and the single follow-up at the end of the treatment. In 2015 Park and co-authors (11), for the first time, used ultrasonography to study the effectiveness of ESWT (1 vs. 3 sessions, 1500 SW per session, energy level 0.030 mJ/mm 2 , frequency 4 Hz) for reducing hypertonicity of the medial gastrocnemius in children with CP. Their case-control study had a relatively small sample size (n = 12) and short follow-up (4 weeks).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that upregulated neovascularization (6), neuroregeneration (7), enzymatic activities (8), anti-inflammatory effect (9), and recruitment of endogenous mesenchymal stromal cells (MSCs) (10) might be involved in the process. Over the last few years several studies have found ESWT to be effective for treating muscle contractures in children with CP via its neuromodulatory and rheological effects (11)(12)(13)(14)(15). However, until now only subjective or operator-dependent assessment tools have been used in order to measure the effects of ESWT on spastic muscles.…”
mentioning
confidence: 99%
“…In our study, ESWT was repeated three times at 1‐week interval. Previous clinical studies have used three sessions of ESWT for the treatment of CTS and spasticity (Ke et al, ; Park, Kwon, Park, & Lee, ). The cumulative effect on the free nerve endings of rats after multiple ESWT sessions resulted in a long‐term antinociceptive effect (Takahashi, Ohtori, Saisu, Moriya, & Wada, ).…”
Section: Discussionmentioning
confidence: 99%